A Core Metabolome Response of Maize Leaves Subjected to Long-Duration Abiotic Stresses - Jaya Joshi (MDPI AG, 2021)
Abiotic stresses reduce crop growth and yield in part by disrupting metabolic homeostasis and triggering responses that change the metabolome. Experiments designed to understand the mechanisms underlying these metabolomic responses have usually not used agriculturally relevant stress regimes. We therefore subjected maize plants to drought, salt, or heat stresses that mimic field conditions and analyzed leaf responses at metabolome and transcriptome levels. Shared features of stress metabolomes included synthesis of raffinose, a compatible solute implicated in tolerance to dehydration. In addition, a marked accumulation of amino acids including proline, arginine, and γ-aminobutyrate combined with depletion of key glycolysis and tricarboxylic acid cycle intermediates indicated a shift in balance of carbon and nitrogen metabolism in stressed leaves. Involvement of the γ-aminobutyrate shunt in this process is consistent with its previously proposed role as a workaround for stress-induced thiamin-deficiency. Although convergent metabolome shifts were correlated with gene expression changes in affected pathways, patterns of differential gene regulation induced by the three stresses indicated distinct signaling mechanisms highlighting the plasticity of plant metabolic responses to abiotic stress.